Beta-Blocker Therapy in Patients With Severe Traumatic Brain Injury: A Systematic Review and Meta-Analysis. Issue 5 (May 2023) - Zagales, Israel; Selvakumar, Sruthi; Ngatuvai, Micah; Fanfan, Dino; Kornblith, Lucy; Santos, Radleigh G.; Ibrahim, Joseph; Elkbuli, Adel
Introduction: Traumatic brain injury (TBI), a leading cause of morbidity and mortality among trauma patients worldwide, poses the risk of secondary neurological insult due to significant catecholamine surge. We aim to investigate the effectiveness and outcomes of beta-blocker administration in patients with severe TBI. Methods: A search through PubMed, EMBASE, JAMA network, and Google Scholar databases was conducted for relevant peer-reviewed original studies published before February 15, 2022. A standard random-effects model was used, as justified by a high Cohen's Q test. Results: Twelve studies met inclusion criteria and were included in the meta-analysis. Severe TBI patients who were administered beta-blockers had a significantly reduced incidence of in-hospital mortality compared to the non-beta-blocker group (14.5% vs 19.2%). However, the beta-blocker group was reported to have a significantly greater number of ventilator days (5.58 vs 2.60 days). Similarly, intensive care unit (9.00 vs 6.84 days) and hospital (17.30 vs 11.02 days) lengths of stay (LOS) were increased in the beta-blocker group compared to those who were not administered beta-blocker therapy, but only the difference in hospital-LOS was significant. Conclusions: Beta-blockers have significantly decreased in-hospital mortality in patients with severe TBI despite being associated with an increase in ventilator days and hospital-LOS. The administration of beta-blocker therapy in the management of severe TBI may be warranted and should be discussed in future guidelines.